DEVELOPING CREATIVE THINKING AND DRAWING SKILLS IN VISUAL ARTS CLASSES - Rustamov Axtam Muxtorovich (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article examines the methods of developing creative thinking and drawing skills in visual arts classes. It analyzes how drawing exercises help students enhance visual perception, compositional skills, and independent decision-making abilities. The article also highlights the pedagogical importance of fostering aesthetic taste, cultural awareness, and creative competencies through practical drawing activities.